Edukasi Makanan Sehat untuk Mencegah Kekurangan Gizi pada anak SDN 7 di Desa Ambawang - Ika Widiastuti; Hari Susanto (Perkumpulan Dosen Program Hibah Indonesia (PDPHI), 2024)
The threat to Indonesian children, including elementary school children, is malnutrition. Knowledge about nutrition must be given from an early age, so that children are able to choose healthy foods for their body's health. Therefore, health education can be provided through educational videos. The aim of this activity is to provide healthy food education to elementary school children. The targets for this activity are students aged 5-12 years or students in grades 3, 4, 5 and 6 of elementary school. The method of implementing activities is carried out offline, namely in large classes. Before starting, participants are asked to complete a pretest and after education they are given a posttest. The results of the activities from 81 participants were 70 participants who completed the pre and post tests. After the education was carried out, participants' knowledge about healthy food increased. This can be seen from the increase in the average participant score from 8.2 to 9.2. This increase in knowledge is expected to prevent malnutrition and increase healthy eating behavior for elementary school children.